Actualidades sobre la taquipnea transitoria del recién nacido - Pastuña Toapanta, Fanny Jaqueline (2022)
ABSTRACT: Introduction: The present research work is focused on determining the current situation on transient tachypnea of the newborn TTN, which is an entity that appears after birth, self-limited, benign that evolves between 24-48 hours, common in newborns by cesarean section and is characterized by respiratory distress secondary to fluid retention in the lungs and secondary air retention. Objective: The main objective was to carry out a bibliographic review of secondary sources of information belonging to recent years, for which a retrospective observational study of analytical cohort on the main news of transient tachypnea of the newborn is presented. Methodology: This study is bibliographic and is based on analytical and scientific research methods that divide the research topic into sections and from them allows to analyze and understand the essential aspects of the study. Literature reviews are developed by properly compiling literature in search engines such as: Medical Subject Headings (MeSH), Scielo, Medline plus, Redalyc, Dialnet, Elsevier, etc. Articles were selected based on inclusion and exclusion criteria. Results and discussion: TTN presents with an incidence of 5.7 cases per 1000 births, being more frequent in term neonates (37-39 weeks) and late preterm infants (34-36.6 weeks). The associated risk factors are the son of a diabetic mother, birth by cesarean section, premature rupture of membrane, presentation dystocia, hypertensive disorders, vitamin D deficiency, prematurity, male sex, its diagnostic approach is by exclusion, being essential to consider the antenatal, natal, postnatal history, and as an aid diagnoses complementary methods such as chest X-ray and pulmonary ultrasound. Conclusion: The treatment of TTN corresponds to measures of ventilatory assistance, oxygen administration, continuous positive pressure, fluid restriction and salbutamol is currently mentioned as one of the treatments that decreases hospital stay. New parameters are also mentioned that would allow predicting the severity of transient tachypnea in the newborn. Reviewed by: Danilo Yépez Oviedo English professor UNACH 0601574692